Intrinsic antiviral immunity of barrier cells revealed by an iPSC-derived blood-brain barrier cellular model - Cheng, Yichen; Medina, Angelica; Yao, Zhenlan; Basu, Mausumi; Natekar, Janhavi P.; Lang, Jianshe; Sanchez, Egan; Nkembo, Mezindia B.; Xu, Chongchong; Qian, Xuyu; Nguyen, Phuong T.T.; Wen, Zhexing; et al. (Cell reports (Cambridge), 2022)
Physiological blood-tissue barriers play a critical role in separating the circulation from immune-privileged sites and denying access to blood-borne viruses. The mechanism of virus restriction by these barriers is poorly understood. We utilize induced pluripotent stem cell (iPSC)-derived human brain microvascular endothelial cells (iBMECs) to study virus-blood-brain barrier (BBB) interactions. These iPSC-derived cells faithfully recapitulate a striking difference in in vivo neuroinvasion by two alphavirus isolates and are selectively permissive to neurotropic flaviviruses. A model of cocultured iBMECs and astrocytes exhibits high transendothelial electrical resistance and blocks non-neurotropic flaviviruses from getting across the barrier. We find that iBMECs constitutively express an interferon-induced gene, IFITM1, which preferentially restricts the replication of non-neurotropic flaviviruses. Barrier cells from blood-testis and blood-retinal barriers also constitutively express IFITMs that contribute to the viral resistance. Our application of a renewable human iPSC-based model for studying virus-BBB interactions reveals that intrinsic immunity at the barriers contributes to virus exclusion. [Display omitted] •iPSC-derived BBB cells recapitulate the in vivo phenotype of neuroinvasive viruses•An iBMEC/astrocyte coculture exhibits high TEER and models viral neuroinvasion•Constitutive expression of IFITM1 selectively inhibits non-neurotropic flaviviruses•Intrinsic expression of IFITMs contributes to broad barrier-based virus restriction Using a stem cell-derived cellular model and a panel of human pathogenic viruses, Cheng et al. show a mechanism by which some viruses can penetrate the blood-brain barrier and cause diseases in the central nervous system.